Persistence and Distortion of Electrical Activity in the LAA 5 Years After Endovascular Occlusion - Kharbanda, Rohit K. (JACC Case Rep, 2020)
This is the first report demonstrating persistence and distortion of electrical activity in the left atrial appendage 5 years after endovascular occlusion with a Watchman device. Electrical conduction is impaired providing an arrhythmogenic substrate for atrial tachyarrhythmias. Localized inflammation may result in structural and electrical remodeling in these patients. (Level of Difficulty: Intermediate.)